Investigating Changes in the Water Requirement of Agricultural Crops in the Jiroft Plain Under Climate Change Impact - Somayeh Afsharipour; Mahdieh Amirinejad; Elham Rafiei Sardooi; Amanollah Soleimani (Nīvār)
The main goal of this research is to investigate the amount of net irrigation requirement of major cultivated crops in Jiroft plain, including potato, onion, wheat, barley, tomatoes and seed corn in the future period (2031-2050) based on different RCP scenarios using LARS-WG6 model is used. The data required in this research include daily precipitation, minimum and maximum temperature and sunshine hours of Jiroft synoptic station (during 1989-2017), which were obtained from Iran Meteorological Organization. First, the ability of LARSWG 6. model to simulate the climatic variables of Jiroft synoptic station in the base period (1989-2017) was investigated. Then, using HadGEM2 model, these variables were simulated during 2050-2031 based on RCP2.6, RCP4.5 and RCP8.5 scenarios. Finally, by calculating the amount of effective precipitation and potential evapotranspiration, the amount of net irrigation requirement of the studied crops was estimated on a monthly scale in the base and the future period, and their changes were evaluated in comparison with each other. Based on the downscaling results of LARSWG 6. Model, and according to RCP2.6, RCP4.5 and RCP8.5 scenarios, the minimum temperature will be increased by 1.3, 2.3 and 2.753 ºC, respectively, the maximum temperature by 0.6, 1.14 and 1.44 ºC, respectively and the average annual precipitation will be decreased by 10, 20 and 27%, respectively. Also, the total amount of net irrigation needs of all crops will increase under all scenarios in the future period, so that the greatest increase will occur under the RCP8.5 scenario.